2019
DOI: 10.1038/s41598-019-50535-z
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Involvement in Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy Predicts Adverse Clinical Outcomes: A Cardiovascular Magnetic Resonance Feature Tracking Study

Abstract: The aim of this study was to investigate left ventricular (LV) global myocardial strain and LV involvement characteristics in patients with arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) and to evaluate their predictive value of adverse cardiac events. Sixty consecutive ARVD/C patients with a definite diagnosis of ARVD/C who underwent CMR examination and thirty-four healthy controls were enrolled retrospectively. The CMR images were analyzed for LV myocardial strain and the presence of LV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…A study evaluated the prognostic role of CMR in patients with definite ( n = 52), borderline ( n = 50), and possible ( n = 73) diagnosis of ARVC, and the results showed that LV involvement (fat infiltration and/or LGE) was an independent predictor of cardiac events [ 113 ]. A recent study demonstrated that LV global strains evaluated by CMR feature tracking could detect early LV dysfunction and predict adverse cardiac events in patients with ARVC [ 114 ].…”
Section: Non-ischemic Cardiomyopathymentioning
confidence: 99%
“…A study evaluated the prognostic role of CMR in patients with definite ( n = 52), borderline ( n = 50), and possible ( n = 73) diagnosis of ARVC, and the results showed that LV involvement (fat infiltration and/or LGE) was an independent predictor of cardiac events [ 113 ]. A recent study demonstrated that LV global strains evaluated by CMR feature tracking could detect early LV dysfunction and predict adverse cardiac events in patients with ARVC [ 114 ].…”
Section: Non-ischemic Cardiomyopathymentioning
confidence: 99%
“… 108 Further, LV global longitudinal strain of >−12.65% is an independent prognostic marker for adverse cardiac outcomes. 109 …”
Section: Arrhythmogenic Cardiomyopathymentioning
confidence: 99%
“…Recent studies have shown that potential LV involvement may develop ahead of significant RV dysfunction in patients with ARVC, although RV dysfunction presents earlier because of its thin and distensible features, which allow it to be primarily affected. [15] One reason for LV involvement in more than half of the patients could be the late presentation and delayed diagnosis due to less awareness and suboptimal medical facilities in this part of the world. is further signifies the importance of this study.…”
Section: Discusionmentioning
confidence: 99%
“…Recent studies have shown that potential LV involvement may develop ahead of significant RV dysfunction in patients with ARVC, although RV dysfunction presents earlier because of its thin and distensible features, which allow it to be primarily affected. [ 15 ]…”
Section: Discusionmentioning
confidence: 99%